Bioimpedance analysis is safe in patients with implanted cardiac electronic devices. Issue 2 (April 2019) - Chabin, Xavier; Taghli-Lamallem, Ouarda; Mulliez, Aurélien; Bordachar, Pierre; Jean, Frédéric; Futier, Emmanuel; Massoullié, Grégoire; Andonache, Marius; Souteyrand, Géraud; Ploux, Sylvain; Boirie, Yves; Richard, Ruddy; et al.
Summary: Background & aims: There is an increase in the number of patients worldwide with cardiac implantable electronic devices (CIEDs). Current medical practice guidelines warn against performing bioimpedance analysis (BIA) in this group of patients in order to avoid any electromagnetic interference. These recommendations restrict using the BIA in patients undergoing heart failure or with nutrition disorders in whom BIA could be of major interest in detecting peripheral congestion and to help guide treatment. The present study was conducted to evaluate whether BIA caused electromagnetic interference in patients having CIEDs. Methods: Patient enrollment was conducted during routine face-to-face consultations for scheduled CIEDs interrogations. Device battery voltage, lead impedance, pacing thresholds and device electrograms were recorded before and after each BIA measurement to detect any electromagnetic interference or oversensing. Results: A total of 200 patients were enrolled. During BIA, no significant changes in battery voltage, lead impedance or pacing thresholds were detected, nor were there any inappropriate over- or undersensing observed in intracardiac electrograms. Furthermore, 6- and 12-month follow-up did not reveal any changes in CIEDs. Conclusions: This study shows no interference in patients equipped with CIEDs and suggests that BIA can be securely performed in these patients. Trial registered under the identifierNCT03045822 .